Ação central da ocitocina no controle da ingestão alimentar : influência do ciclo estral - Fontes, Rodrigo Figueiredo (2012)
In addition to stimulation of uterine contraction and milk ejection, oxytocin (OT) acts on neural circuits that control food intake. This study aimed to investigate the gonadal modulation of ocitocinergic control on food ingestion. Female Wistar rats with at least three regular cycles were monitored for 15 days and underwent implantation of cannula into the lateral ventricle. After the surgery it was accompanied three more cycles and which remained regular, were fasted for 24 hours and received intracerebroventricular microinjection (5 uL) of OT (5 UI, 1 g/L) or phosphate buffered saline (PBS). Immediately after the infusions, a balanced ration was offered and measured the amount of food consumed by 90 minutes. Approximately 12% of rats submitted to cannula implantation surgery altered the regularity of the cycle phase and remained at metaestrous, eventually presenting diestrus phase. Thirty-one rats were subjected to implantation of cannulas into the lateral ventricle, 16 have received microinjections (5 uL) of PBS and 15 have received microinjections (5 uL) of OT (5 UI). After 24 hours of fasting, 8 rats at proestrus showed an average food intake of 2,45 ± 0,28 g/100g, while 8 rats al metaestrous presented an average food intake of 2,17 ± 0,26 g/100g of body mass for 90 minutes after resubmission of chow, no presenting significant differences between groups (p<0,05). Of the 16 rats subjected microinjection of PBS, 8 were at metaestrous and 8 in proestrus on the day of experiment. After 24 hours of fasting, the eight rats in metestrus showed an average food intake of 2,17 ± 0,25 g/100g, while in the proestrus, the eight rats presented an average food intake of 2,45 ± 0,28 g/100g, no presenting significant differences between groups (p<0,05). Of the fifteen rats subjected microinjection of oxytocin, 7 were at metaestrous and 8 in proestrus. After 24 hours of fasting, the 7 rats in metestrus showed an average food intake of 1,21 ± 0,15 g/100 g, while in the proestrus, the 8 rats presented an average food intake of 1,61 ± 0,26 g/100 g of body mass for 90 minutes after reintroduction of food, significant differences between groups (p<0,05). Regarding the processing of immunofluorescence revealed the expression of c-Fos in the paraventricular nucleus (PVN) and supraoptic (SON) of rats in metestrus and proestrus phases, respectively, microingetadas (icv) with saline or oxytocin in the conditions of representation feed after fasting (24 hours). Thus, our results show that oxytocin has a central action on behavior food intake and that of the phases of the estrous cycle does not modulate the inhibitory action of oxytocin in the control of food intake.